Biological characterization of fungal endophytes isolated from agarwood tree Aquilaria crassna Pierre ex Lecomte - Chi, Hoang Kim; Cuong, Le Huu; Hang, Tran Thi Nhu; Luyen, Nguyen Dinh; Ha, Tran Thi Hong; Huong, Le Mai (Vietnam Journal of Biotechnology, 2016)
In recent years, a considerable number of studies on the role of microbes in agarwood production have been carried out in plants of the species Aquilaria. Based on the fact that there is a relationship between the microorganisms residing inside the plant and the agarwood formation, we isolated and characterized endophytic fungi associated with A. crassna samples collected from Southern Vietnam. Morphological identification and DNA barcoding analysis of the fungal endophytic isolates indicated that they were classified at least into three groups of diverse genera: Geotrichum, Fusarium and Colletotrichum belonging to families Dipodascaceae, Nectriaceae and Glomerellaceae, respectively.  Noteworthy, Geotrichum candium strain SHTr1 isolated from a dark colored woody sample of agarwood was able to produce a fruity odor and exhibited a slight antimicrobial activity against the test bacterium Staphylococcus aureus. Another fungal isolate, Fusarium verticillioides SHTr3’s, showed a moderate antimicrobial activity against a test Gram positive bacteria Bacillus subtillis and S. aureus with MIC values at 50 μg.mL-1. At 200 μg.mL-1, the ethyl acetate extracts of fungal isolates F. verticillioides SHTr3 and Colletotrichum truncatum SHTrHc7 were found to have comparable scavenging abilities on DPPH-free radicals with 53.87 and 71.82%, respectively. The present results contribute to a depiction of a diverse fungal endophytic community in Vietnamese agarwood plant A. crassna and provide important information for further understanding of the role of endophytic fungi in agarwood formation and therapeutic applications of host plants in general.